EXPERIMENTAL STUDY FOR OXIDATION OF PHENOL BY FENTONS REAGENT (Journal of Engineering, 2010)
The oxidation of phenol in aqueous solution was studied at atmospheric pressure in a batchreactor. Fenton reaction was used to degrade this component. Phenol (50 - 100 ppm) oxidation was carried out in the acidic medium range of (pH=2.7 - 5.8) under mild conditions of temperature (28 - 48°C), stochiometric excess percentage of H2O2 (S.EH2O2%) of (0 - 100%), and Fe(II) to phenol concentrations ratio of (0 - 0.63). The results indicate that the oxidation by Fenton reaction was an efficient method to eliminate phenol, also the amount of catalyst and temperature had the large effect on the phenol degradation. Finally the simple kinetic model for the reaction was established.